Comprehensive effect of tuning Cu/SAPO-34 crystals using PEG on the enhanced hydrothermal stability for NH3-SCR. Issue 23 (31st October 2021) - Lin, Qingjin; Liu, Shuang; Xu, Shuhao; Xu, Shi; Pei, Mingming; Yao, Pan; Xu, Haidi; Dan, Yi; Chen, Yaoqiang
Abstract : PEG fabricates advantageous hierarchical zeolite crystals, enhancing the high-temperature and low-temperature hydrothermal stability of Cu/SAPO-34. Abstract : The high-efficiency NH3 -assisted selective catalytic reduction (NH3 -SCR) technology continues to attract wide attention in diminishing harmful nitrogen oxides (NO x ) from diesel exhausts. However, one of the crucial challenges is the deteriorated performance of NH3 -SCR catalysts during the regeneration of the diesel particulate filter (high-temperature hydrothermal conditions). To address it and meet the need for environmental protection, we tried to adopt poly(ethylene glycol) (PEG) to fabricate intact hierarchical zeolite crystals and finally enhance the hydrothermal stability. The characterization evidences that the stable Si–O–Al structure exists in this optimal structure after the hydrothermal treatment at 800 °C, which provides some favorable intermediates on the Cu–zeolite in the low-temperature (150–350 °C) region, particularly the activation of NO into bridged nitrates on adjacent isolated copper sites. Besides, Cu/SAPO-34 catalysts modified with PEG still better convert NO x into N2 after the hydrothermal aging at 70 °C for 10 hours. Our study thus provides a new idea for improving the hydrothermal stability of the Cu/zeolite NH3 -SCR catalyst to remove NO x . This robust hydrothermal stability of Cu/zeolite helps its better sustainable application under harsh NO x removal conditions.